2022
DOI: 10.1186/s12915-022-01461-6
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome’s fiber degradation profile and its relationship with the host diet

Abstract: Background The relationship between the gut microbiome and diet has been the focus of numerous recent studies. Such studies aim to characterize the impact of diet on the composition of the microbiome, as well as the microbiome’s ability to utilize various compounds in the diet and produce metabolites that may be beneficial for the host. Consumption of dietary fibers (DFs)—polysaccharides that cannot be broken down by the host’s endogenous enzymes and are degraded primarily by members of the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Our approach complements other methods to describe how gut microbiome function is structured 42 . Importantly, it provides much needed quantitative biological data to inform computational models 43 .…”
Section: Energy Flow Context Flowmentioning
confidence: 99%
“…Our approach complements other methods to describe how gut microbiome function is structured 42 . Importantly, it provides much needed quantitative biological data to inform computational models 43 .…”
Section: Energy Flow Context Flowmentioning
confidence: 99%
“…Given the vast diversity of substrates available, finer CAZyme subfamily resolutions will be necessary to aid the discovery of other prebiotic associated genes to allow for a greater scale of precision. Improvements in CAZyme annotation and curation frameworks as described in Cohen & Borenstein [61]will be especially beneficial in capturing fiber degradative profiles and subsequent biomarker discovery across fiber intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence of functional redundancy in the gut microbiome [62,63], shifts in CAZyme composition have previously been observed in response to different substrate feeding [64,65]. Likewise, in population-based studies, CAZyme profiles have also been shown to reflect dietary preferences and the type of glycans that microbes encounter in the gut [61,66,67]. Moreover, strain heterogeneity in CAZyme profiles within the same genus has been described such as in species of Bifidobacterium and Prevotella [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…1), featuring glycan substrate prediction for both CAZymes and CGCs (Table 1). This substrate prediction function is critical to microbiome researchers who are interested in knowing not only what CAZyme families exist in their genomes or metagenomes, but also what glycan substrates can be metabolized in their samples (e.g., by bacterial isolates or microbiota) [42][43][44] . For example, a paper published in 2018 compared human gut microbiomes of two groups of patients with type 2 diabetes 45 .…”
Section: Improved Dbcan Functionsmentioning
confidence: 99%
“…In addition to assembly-based approaches, the assembly-free strategy is also used, e.g., in the popular general metagenomic functional annotation tool HUMAnN3 57 and the inferred fiber degradation profile tool (IFDP) 43 . The assembly-free approach does not need run_dbcan but rather directly searches sequencing reads against the CAZy annotated protein sequence database (i.e., CAZyDB).…”
Section: Experimental Designmentioning
confidence: 99%